2016
DOI: 10.1111/hdi.12488
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of sodium profiling techniques and the impact on intradialytic hypotension

Abstract: AimsTo assess the effectiveness of haemodialysis sodium profiling techniques Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Despite the significant improvements and advanced dialysis technology [35], renal transplantation still remains the treatment of choice for end stage renal disease patients, and over the past decades the overall survival rate of kidney grafts has improved consistently. Moreover, because of the wide gap between organ supply and demand, there is a growing number of patients with kidney failure who inexorably accumulate on renal transplant waiting lists [6], as well as the number of renal transplant (RT) recipients with functioning grafts going to be exposed to pathogens [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant improvements and advanced dialysis technology [35], renal transplantation still remains the treatment of choice for end stage renal disease patients, and over the past decades the overall survival rate of kidney grafts has improved consistently. Moreover, because of the wide gap between organ supply and demand, there is a growing number of patients with kidney failure who inexorably accumulate on renal transplant waiting lists [6], as well as the number of renal transplant (RT) recipients with functioning grafts going to be exposed to pathogens [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium profiling is a modified method of sodium gradient dialysis during which DNa follows a time‐dependent profile. It can increase the extracellular volume and prevent intradialytic discomforts, such as hypotension, muscle cramps, and disequilibrium syndrome; some studies have found an increase in IDWG and thirst during the sodium‐profiled dialysis therapy . In a randomized cross‐over study, the DNa was changed from 155 ‐ 160 mmol/L in the beginning to 140 mmol/L in the last hour of dialysis during the intervention period.…”
Section: Sodium Profilingmentioning
confidence: 99%
“…Intradialytic hypotension may accelerate RKF loss via ischemic insults and can be prevented by sodium and water restriction, dialysate cooling, sodium profiling (which is reserved for short-term use), changing the ultrafiltration profile, and acetate-free HDF [67-70]. Using loop diuretics in hemodialysis patients with considerable RKF can also lower interdialytic weight gain and eventually benefit the preservation of RKF [71].…”
Section: How To Protect Rkfmentioning
confidence: 99%